New Approaches for Absolute Quantification of Stable‐Isotope‐Labeled Peptide Standards for Targeted Proteomics Based on a UV Active Tag. Issue 10 (20th May 2020) - Schnatbaum, Karsten; Solis‐Mezarino, Victor; Pokrovsky, Daniil; Schäfer, Frederike; Nagl, Dennis; Hornberger, Lars; Zerweck, Johannes; Knaute, Tobias; Avramova‐Nehmer, Julia; Schutkowski, Mike; Hornung, Veit; Wenschuh, Holger; et al.
Abstract: Targeted proteomics depends on the availability of stable isotope labeled (SIL) peptide standards, which for absolute protein quantification need to be absolutely quantified. In the present study, three new approaches for absolute quantification of SIL peptides are developed. All approaches rely on a quantification tag (Qtag) with a specific UV absorption. The Qtag is attached to the peptide during synthesis and is removed by tryptic digestion under standard proteomics workflow conditions. While one quantification method (method A) is designed to allow the fast and economic production of absolutely quantified SIL peptides, two other methods (methods B and C) are developed to enable the straightforward re‐quantification of SIL peptides after reconstitution to control and monitor known problems related to peptide solubility, precipitation, and adhesion to vials. All methods yield consistent results when compared to each other and when compared to quantification by amino acid analysis. The precise quantitation methods are used to characterize the in vivo specificity of the H3 specific histone methyltransferase EZH2.